Security sage's guide to hardening the network infrastructure - Andrés, Steven (Syngress Pub., 2004)
Security Sage's Guide to Hardening the Network Infrastructure focuses on both perimeter and internal networks, giving IT and security administrators a complete picture of how they should design and protect their enterprises. Other books may concentrate on perimeter security or host configuration yet ignore the infrastructure connecting the two. While others tend to focus on theory and basic security background, this publication will dive right into the content and help provide real solutions to common IT security problems.